TEORIA CONTRATUAL CONTEMPORÂNEA: NOVOS PARADIGMAS. - Marcelo Farina de Medeiros; Juliane Nagafugi de Souza Costa (Universidade do Oeste Paulista, 2016)
This study uses the deductive method, dialectical and empirical for through doctrinal, jurisprudential and legal research to contribute to the analysis of contractarian theories, their historical context and application period. With the liberal revolutions sought to autonomy in social relations, both horizontal and vertical. In this context came the classical contractual theory, based on pacta sunt servanda. However, with the promotion of social relations and weakness of the negotiating phase in the execution of legal, especially with the advent of the accession agreement, Law Democratic State principles came to be harmed, resulting in the need for state action to the equilibrium search of legal relations. It comes, then, the contemporary theory of contracts, to prioritize for the protection of social values, bringing as legal object to be protected the person, instead of the bargaining act. Therefore we see a paradigm break, occasioning a milestone in negotiation law, from which the contract social function shall govern the extent of the autonomy of the parties.